Building a collaborative cloud platform to accelerate heart, lung, blood, and sleep research - Ahalt, Stan; Avillach, Paul; Boyles, Rebecca; Bradford, Kira; Cox, Steven; Davis-Dusenbery, Brandi; Grossman, Robert L; Krishnamurthy, Ashok; Manning, Alisa; Paten, Benedict; Philippakis, Anthony; Borecki, Ingrid; et al. (Journal of the American Medical Informatics Association : JAMIA, 2023)
Abstract Research increasingly relies on interrogating large-scale data resources. The NIH National Heart, Lung, and Blood Institute developed the NHLBI BioData CatalystⓇ (BDC), a community-driven ecosystem where researchers, including bench and clinical scientists, statisticians, and algorithm developers, find, access, share, store, and compute on large-scale datasets. This ecosystem provides secure, cloud-based workspaces, user authentication and authorization, search, tools and workflows, applications, and new innovative features to address community needs, including exploratory data analysis, genomic and imaging tools, tools for reproducibility, and improved interoperability with other NIH data science platforms. BDC offers straightforward access to large-scale datasets and computational resources that support precision medicine for heart, lung, blood, and sleep conditions, leveraging separately developed and managed platforms to maximize flexibility based on researcher needs, expertise, and backgrounds. Through the NHLBI BioData Catalyst Fellows Program, BDC facilitates scientific discoveries and technological advances. BDC also facilitated accelerated research on the coronavirus disease-2019 (COVID-19) pandemic.